POLITENESS STRATEGY ANALYSIS ON EXPRESSIVE UTTERANCES FOUND IN “LAND BEFORE TIME XIV” MOVIE - Pebriyani, Ni Putu Rita; Maharani, Putu Devi; Utami, Ni Made Verayanti (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study aims to find out the politeness strategy applied in the expressive utterances produced by the characters in Land before Time XIV movie. The data of this study is taken from the movie upload in Daily Motion website and movie script download from Fandon website. This study uses two theories, first from Brown and Levinson (1987) about politeness strategy to discover what types of politeness strategy that occurs on the expressive utterances in the movie. Second theory from Searle (1969) about the expressive function to find out what kind of expressive function found in the utterances. In this research, the method used to analyzed the data is qualitative research method. The result of this study found all the types of politeness strategy are applied in the utterances produced by the characters. Besides, all the characters are expressing some function of speech, there are showing regret, showing acceptance, appreciation, praising, condoling, complaining, and criticizing.